Anna G. Piotrowska, „O muzyce i filmie. Wprowadzenie do muzykologii filmowej”, Kraków 2014 - Bernatowicz, Wojciech (Muzyka, 2018)
Recenzja książki: Anna G. Piotrowska, „O muzyce i filmie. Wprowadzenie do muzykologii filmowej”, Kraków 2014